2019
DOI: 10.1111/ped.13892
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory values in Japanese children with newly diagnosed inflammatory bowel disease

Abstract: Background Laboratory data in children with newly diagnosed inflammatory bowel disease (IBD) have been reported from Europe and North America, but not Asia. The aim of this study was to clarify laboratory data in Japanese children with newly diagnosed IBD, and to compare them with those in Western reports. Methods We retrospectively reviewed patients <16 years old, newly diagnosed with ulcerative colitis (UC) or Crohn's disease (CD) at Kurume University Hospital between January 2008 and December 2015. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…Although endoscopy can never be completely replaced, fecal and blood biomarkers can provide noninvasive, repeatable, and cost-effective assays for disease monitoring in IBD. 28 , 29 Compared with blood indicators, fecal biomarkers such as FC that directly contact inflamed intestines are more desirable for clinical routines. This research provided the first evidence that OSM was a novel fecal biomarker, along with FC, and their combination was more beneficial for IBD management in specific clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…Although endoscopy can never be completely replaced, fecal and blood biomarkers can provide noninvasive, repeatable, and cost-effective assays for disease monitoring in IBD. 28 , 29 Compared with blood indicators, fecal biomarkers such as FC that directly contact inflamed intestines are more desirable for clinical routines. This research provided the first evidence that OSM was a novel fecal biomarker, along with FC, and their combination was more beneficial for IBD management in specific clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the trends of some parameters in pediatric patients with IBD have been reported to differ between UC and CD at initial diagnosis. Patients with CD have lower albumin and hemoglobin levels and higher erythrocyte sedimentation rates, C-reactive protein levels, and platelet counts than those with UC [ 36 37 38 39 ]. In our study, laboratory parameters were compared between the cCD and rUC groups.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to the findings of a previous study, which reported that hypoalbuminemia could be a predictor of the diagnostic change from IBDU to CD [ 12 ]. Other studies have emphasized that differences in laboratory parameters could be affected by the distribution and severity of disease [ 37 39 ]. Mack et al [ 38 ] have reported that patients with colon-only CD are more likely to show normal laboratory parameters than those with CD involving the small intestine or the upper gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Збільшення кількості лімфоцитів >37%, моноцитів >11%, еозинофілів >5% документована у пацієнтів всіх груп, але достовірних відмінностей їх показників знайдено не було (p>0,05). Отримані нами результати співпадають з даними літератури [24,29].…”
unclassified
“…Наведене дозволяє зробити висновок про те, що клінічні симптоми тісно пов'язані з такими показниками гемограми як гемоглобін, лейкоцити, тромбоцити, ШОЕ, а також концентрація фекального кальпротектину, γ-глобулінів, показника АГ-коефіцієнту, які можуть бути використані як критерії перебігу захворювання та моніторингу базової терапії пацієнтів. Наші дані збігаються з результатами щодо прогностичної значимості комбінації лейкоцитів, тромбоцитів, ШОЕ для виявлення тяжкості ВК [23,29].…”
unclassified